Menopausal women's expectations towards hormone replacement therapy - Bielawska-Batorowicz, Eleonora; Rutkowska, Elżbieta (Menopause Review/Przegląd Menopauzalny, 2003)
Aims: The aim of the study was to look at patients’ expectations related to hormone replacement therapy (HRT) and at stability of these expectations during several month of treatment. The relationship between menopausal symptoms, expectations and the decision to continue HRT was also analysed. Material and method: Thirty eight menopausal women (mean age 52.4) eligible for HRT were tested twice – just before pursuing HRT and after 4 months of treatment. Menopause Symptoms List by J. Perz and HRT Expectations Questionnaire by E. Rutkowska were administered on both occasions. Results: Women expected that HRT would have an impact on their psychological and physical well-being. They expected also regular medical check-up and discussion about their concerns related to treatment. All these expectations remained stable during 4 months period and were not related to menopausal symptoms recorded before HRT treatment. The decision to continue with HRT was not related to psychological, physical and sexual changes.